2021
DOI: 10.1088/1755-1315/743/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Growth response and vital statistics of fat and thin tailed sheep with soybean husk supplements in Malang District

Abstract: This study aimed to determine the pattern of body weight gain and vital statistical measures of fat sheep and thin tails and to determine the response of local sheep production to the provision of soybean meal/skin. The method used in this research is a case study and experimental. The sampling technique is done by a simple random method on vital statistical measures performed by measuring the chest (using a measuring tape) and body length (using a measuring stick). The tabulated data were first analyzed for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
2
1
1
Order By: Relevance
“…These results are lower than the measurements in the study by [10], where they found an average chest circumference of 72.80 cm for 60 Fat-Tailed Sheep aged 1 to 2 years. Conversely, the findings are higher than the results from [11], which reported an average chest circumference of 63 ± 3.98 cm for Fat-Tailed Sheep.…”
Section: Morphometric Traits and Body Weight Of Fat-tailed Sheepcontrasting
confidence: 83%
“…These results are lower than the measurements in the study by [10], where they found an average chest circumference of 72.80 cm for 60 Fat-Tailed Sheep aged 1 to 2 years. Conversely, the findings are higher than the results from [11], which reported an average chest circumference of 63 ± 3.98 cm for Fat-Tailed Sheep.…”
Section: Morphometric Traits and Body Weight Of Fat-tailed Sheepcontrasting
confidence: 83%
“…Sesuai dengan pendapat Mudawamah et al (2023), bahwa bangsa ternak yang berbeda akan mempunyai ciri fenotipe yang berbeda termasuk komponen darah. Selain itu, perbedaan antara studi-studi ini mungkin disebabkan oleh perbedaan breed dan nutrisi (Mudawamah et al, 2022;Yenilmez et al, 2021;Nasich et al, 2021).…”
Section: Nilai Eritrosit Dari Berbagai Fase Reproduksi Induk Domba Sa...unclassified
“…Garut and Sapudi sheep are local sheep in Indonesia that are kept as meat producers and play an essential role in the local community, so their population must be increased (Heriyadi, 2005;Mirella et al, 2022;Mudawamah et al, 2022;Nasich et al,).…”
Section: Introductionmentioning
confidence: 99%